First observation of a nuclear s-state of a Ξ hypernucleus, ^15_ΞC. (22nd July 2021) - Yoshimoto, M; Ahn, J K; Bassalleck, B; Ekawa, H; Endo, Y; Fujita, M; Han, Y; Hashimoto, T; Hayakawa, S H; Hicks, K; Hoshino, K; Hoshino, S; et al.
Abstract: Bound systems of Ξ^- –^14_N are studied via Ξ^- capture at rest followed by emission of a twin single-Λ hypernucleus in the emulsion detectors. Two events forming extremely deep Ξ^- bound states were obtained by analysis of a hybrid method in the E07 experiment at J-PARC and reanalysis of the E373 experiment at KEK-PS. The decay mode of one event was assigned as Ξ^-+^14\! \!\!N→^5_Λ\!\!\!He + ^5_Λ\!\!He + ^4\!\!He + n . Since there are no excited states for daughter particles, the binding energy of the Ξ^- hyperon, B_Ξ^-, in the ^14_N nucleus was uniquely determined to be 6.27 ± 0.27 MeV. Another Ξ^- –^14_N system via the decay ^9_ΛBe + ^5_Λ\!\!\!He + n brings a B_Ξ^- value, 8.00 ± 0.77 MeV or 4.96 ± 0.77 MeV, where the two possible values of B_Ξ^- correspond to the ground and the excited states of the daughter ^9_ΛBe nucleus, respectively. Because the B_Ξ^- values are larger than those of the previously reported events (KISO and IBUKI), which are both interpreted as the nuclear 1p state of the Ξ^- –^14_N system, these new events give the first indication of the nuclear 1s state of the Ξ hypernucleus, ^15_ΞC .